Visualization techniques of the inferior alveolar nerve (IAN): a narrative review - Weckx, Annelies (Surg Radiol Anat, 2015)
PURPOSE: The purpose of this study was to produce an overview of the present visualization techniques of the inferior alveolar nerve (IAN) in order to reduce the rates of nerve damage after third molar (M3) removal and bilateral sagittal split osteotomy (BSSO). METHODS: An electronic literature search was performed of the English-language scientific literature published prior to December 31, 2014 using the LIMO KU Leuven search platform. Information on the specifications of the different imaging techniques, their clinical application, advantages, disadvantages, and duration was extracted from 11 reports. RESULTS: Five methods for IAN visualization were obtained from the search results, which are cone-beam computed tomography (CBCT) and automatic extraction of the IAN canal using computed tomography (CT), magnetic resonance imaging (MRI), panoramic radiography, endoscopy, and ultrasonographic visualization. CONCLUSION: The results of this study suggest that high-resolution MRI is the most commonly used method for direct visualization of the IAN. Six out of the eleven manuscripts use this technique. Recently, there have been some (experimental) modifications to the conventional MRI in the form of diffusion tensor tractography (DTT), phase-contrast magnetic resonance angiography (PC-MRA), and dental MRI. Future studies will focus on an intraoperative application of MRI to visualize the IAN during surgery.